Breaking barriers: how the rural poor engage in tourism activities without external support in selected Iranian villages - Torabi, Zabih-Allah (Frontiers in Sustainable Tourism, 2024)
Background This study examines the participation of the rural poor in tourism activities without external support in selected Iranian villages, addressing the research gap on their direct involvement in formal and informal tourism businesses. Methodology A qualitative approach was employed, utilizing face-to-face semi-structured interviews with 65 participants from three villages near Turan National Park in Shahrud, Iran. Data were analyzed using thematic analysis. Findings Results indicate that the rural poor actively engage in tourism. This participation encompasses seeking formal employment in tourism facilities, engaging in informal activities, and acquiring relevant knowledge and skills. The study highlights the significant potential of informal tourism businesses in increasing opportunities for low-income individuals, despite challenges such as lack of capital and legal protection. Conclusion The findings demonstrate that even without external assistance, the rural poor find ways to participate in and benefit from tourism activities. Both formal and informal tourism activities play important roles in poverty alleviation efforts. The study emphasizes the need for targeted interventions to support the rural poor's participation in the tourism sector and harness tourism's potential for poverty reduction in rural areas.